2016
DOI: 10.2147/ijn.s117511
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of nanostructured lipid carrier-based hydrogel for topical delivery of 5-fluorouracil

Abstract: The aim of this study was to develop a nanostructured lipid carrier (NLC)-based hydrogel and study its potential for the topical delivery of 5-fluorouracil (5-FU). Precirol ® ATO 5 (glyceryl palmitostearate) and Labrasol ® were selected as the solid and liquid lipid phases, respectively. Poloxamer 188 and Solutol ® HS15 (polyoxyl-15-hydroxystearate) were selected as surfactants. The developed lipid formulations were dispersed in 1% Carbopol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(36 citation statements)
references
References 38 publications
1
33
0
Order By: Relevance
“…Determining the particle size is of great importance in nanostructured formulations as the small particle size contributes to a greater interfacial area, which can then provide better drug partitioning and absorption at the skin surface. [47][48][49] Zeta potential Zeta potential (ZP) is a key factor for evaluation of the stability of nano dispersion. The ZP determination is based on particle electrophoretic mobility in aqueous medium.…”
Section: Particle Size Measurementmentioning
confidence: 99%
“…Determining the particle size is of great importance in nanostructured formulations as the small particle size contributes to a greater interfacial area, which can then provide better drug partitioning and absorption at the skin surface. [47][48][49] Zeta potential Zeta potential (ZP) is a key factor for evaluation of the stability of nano dispersion. The ZP determination is based on particle electrophoretic mobility in aqueous medium.…”
Section: Particle Size Measurementmentioning
confidence: 99%
“…The use of chemotherapeutic agents is a major strategy for destroying cancer cells and maintaining normal cell development in cancer patients [1]. 5-Fluorouracil (5-FU), an antimetabolic chemotherapeutic agent used mostly to treat various types of cancer and tumors, is a fluorinated pyrimidine whose anticancer activity is based on its capacity to interfere with nucleotide metabolism, as well as RNA and DNA synthesis [2][3][4][5]. However, several adverse effects are associated with 5-FU therapy, including nausea, vomiting, diarrhea, myelosuppression, and intestinal mucositis [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the skin retention study observed high retention of 5-Fu from NLC gel (91.256 ± 4.56 lg/cm 2 ) compared with pure drug (12.23 ± 3.86 lg/cm 2 ). Overall, results indicated that 5-fluorouracil incorporated NLC potentially delivered in skin layers with minimal irritation [81].…”
Section: Strategic Therapeutic Intervention Utilizing Advance Nanocarmentioning
confidence: 86%